Synthesis, Characterisation and Antimicrobial Screening of Aminobenzylated Mannich Bases of Acetamide and Urea - Mohamed Kasim, A.N.; Venkatesa Prabhu, G. (Asian Journal of Chemistry, 2010)
The compound N-(1-piperidino-4-methylbenzyl)acetamide (1a), N-( 1-piperidino-4-chlorobenzyl)acetamide (1b), N,N' -bis (1- piperidino-4-methylbenzyl)urea (2a) and N,N'-bis (1-piperidino-- 4-chlorobenzyl)urea (2b) have been synthesised by condensing piperidine and acetamide/urea with 4-methylbenzaldehyde/4- chlorobenzaldehyde. The compounds have been characterised on the basis of microanalytical, IR, 1H and 13C NMR and mass spectral data and screened for their antimicrobial activity against grampositive and gram-negative bacteria.